Paleoseismic Analysis of the Walanae Fault Zone in South Sulawesi, Indonesia - Asri Jaya; Osamu Nishikawa; Sahabuddin Jumadil (Geological Agency, 2023)
The most seismogenic fault of South Sulawesi region is Walanae Fault, which has a moderate seismicity history with magnitudes ranging from Mw 4 to Mw 5. The largest earthquake occurred in 1997 with a magnitude of Mw 5.9. After the Donggala-Palu earthquake assailed Sulawesi Island in 2018, the fault in this region were reactivated, including the Walanae Fault system that has pair parallel faults, West Walanae Fault (WWF) and East Walanae Fault (EWF). This fault zone has a 150-km-long and 3-km-wide fault traces, and should have seismicity potential to produce larger earthquakes than the events measured to date. The resulting radiocarbon ages obtained from the dating of organic samples collected on two tranches along with the EWF support that the Walanae Fault zone has a longer earthquake history in the ranges of 4,000 BP (3,050 cal BP and 3,990 cal BP) and 100-300 AD (101 AD pMC and 340 cal BP). The results of age evidence suggest that the Walanae Fault system is an active fault, and must remain of concern as an earthquake source with potential hazards in the region, comprising the West Walanae Fault (WWF) and the East Walanae Fault (EWF). Both faults are separated by a narrow lowland area of Walanae Depression (25 km). The lowland area sandwiched by these two faults harboring a potential seismic amplification that might be generated by thick sediment filled the lowland. Keywords: seismicity, earthquake, radiocarbon dating, Walanae Fault